Control of Landslide by Lowering Groundwater Level Through Induced Pumping Method - Nur Hanisah Binti Ismail, Nur Hanisah (Universiti Teknologi Petronas, 2009)
It is well recognized that groundwater table has important role on the slope failure. Slope failure is one of the serious hazards to the community Landslide tragedies have caused substantial loss of life and damage to property and infrastructure. The purpose of this project is to examine the soil moisture and its shear strength when ground water table is high due to heavy rainfall. This project also attempts to find a method of controlling groundwater table at the slope as induced by pumping method. This project is based on a laboratory experimental and slope modeling that would reduce the moisture content of the soil by pumping method. It is expected that the pumping method could control the slope failure. The experimental work was conducted base on the soil in Bukit Kledang. The soil is silty clay type and has an intermediate value of plasticity index. The parameter for shear strength is also in the range that is appropriate for the soil, which is 5kPa of cohesion and 25° of friction angle. The analysis from the SLOPE/W software shows that at the existing ground water level, the safety index is lower than 1. Lowering groundwater level improves the stability of the slope as indicated by the improve value of factor of safety (FOS). For the slope height of 10m, the reduction of groundwater level could increase FOS froml. 153 to 1.310 however for the slope of greater height such as 100m; the reduction could only increase from 0.659 FOS to 0.971 FOS. Thus, other safety measure is necessary for high slope